RETAIL MARKETING STRATEGIES AND INNOVATIONS IN THE PRACTICE OF A RETAIL CHAIN - Jakub Berčík; Jana Gálová; Elena Horska (Polityki Europejskie, Finanse i Marketing)
Each retail activity, regardless its financial base is related to applying various marketing tools and territorial strategies. At present, the application of key retail marketing is associated with a wide range of activities, developing retailer, allocating sufficient capital and adapting to the market conditions of the area. Successful retail companies have become easy to copy, therefore they are constantly trying to innovate and looking for new opportunities in the battle for their customers. In the domestic market which is torn by strong multinational competitors, our retailers are able to ensure the right timing and adjusting marketing only by forming alliances such as COOP Jednota Slovakia. Using guided dialogue and laser device for measuring the distance we have revealed many deficiencies in the implementation of unified marketing strategies and we obtained data for the calculation of location indicators in different types of sales forms. The paper also includes the evaluation of areal retail marketing and its subsequent adaptation to the conditions of the region, together with the strategic deployment and innovation of different types of stores in the area. In the conclusions, we give suggestions for more effective retail marketing, innovations and application of positioning strategies that will contribute to the increase in sales and the efficiency in the consumer cooperative COOP Jednota Brezno.